2014
DOI: 10.1128/aac.01254-13
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of SQ641-NE against Mycobacterium tuberculosis

Abstract: A phospholipid-based nanoemulsion formulation of SQ641 (SQ641-NE) was active against intracellular Mycobacterium tuberculosis in J774A.1 mouse macrophages, although SQ641 by itself was not. Intravenous (i.v.) SQ641-NE was cleared from circulation and reached peak concentrations in lung and spleen in 1 h. In a murine tuberculosis (TB) model, 8 i.v. doses of SQ641-NE at 100 mg/kg of body weight over 4 weeks caused a 1.73 log 10 CFU reduction of M. tuberculosis in spleen and were generally bacteriostatic in lungs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…38,39 In a mouse model of chronic M. tuberculosis infection, SQ641 was able to reduce bacterial lung burden by 1.0-1.5 log 10 CFU. 40 However, its lipophilicity and low water solubility has led to studies with delivery vehicles 41 as well as further chemical modifications to improve intracellular activity. 42 A capuramycin analogue, UT-01320, inhibits bacterial RNA polymerases and has been shown to work in synergy with SQ641 to inhibit M. tuberculosis H37Rv growth to a greater extent than each molecule alone.…”
Section: Mycinsmentioning
confidence: 99%
“…38,39 In a mouse model of chronic M. tuberculosis infection, SQ641 was able to reduce bacterial lung burden by 1.0-1.5 log 10 CFU. 40 However, its lipophilicity and low water solubility has led to studies with delivery vehicles 41 as well as further chemical modifications to improve intracellular activity. 42 A capuramycin analogue, UT-01320, inhibits bacterial RNA polymerases and has been shown to work in synergy with SQ641 to inhibit M. tuberculosis H37Rv growth to a greater extent than each molecule alone.…”
Section: Mycinsmentioning
confidence: 99%
“…In general, emulsions are cloudy but the nanoemulsions have translucent and clear appearance. Nikonenko et al (2014) developed phospholipid-based nanoemulsion system of SQ-641-NE which was found to be active against Mycobacterium tuberculosis. Different examples of antitubercular drug loaded emulsion systems are given in Table 3.…”
Section: Nanoemulsionmentioning
confidence: 99%
“…Surface-modified nano-emulsions have been developed to reach animals and human liver in a similar way to chylomicrons [ 314 , 315 ]. SNEDDSs can drastically increase the concentration of the drug in liver and/or spleen and can be a smart way to reach these organs [ 316 , 317 , 318 ].…”
Section: Advancements In Sneddssmentioning
confidence: 99%